"We all have coping and communication problems". Experiences of stroke survivors living with aphasia and graduate student clinicians who participated in a telehealth interprofessional psychoeducation and wellness group. Issue 3 (4th March 2023) - Kincheloe, Harley; Off, Catherine; Murphy, Molly; Griffin-Musick, Jenna; Murray, Kirsten; Jakober, Dawson
ABSTRACT: Background: Aphasia negatively impacts functional daily communicative participation, participation in life's domestic, educational, vocational and recreational roles, psychosocial well-being and social relationships, and overall quality of life, thereby increasing the need for holistic, comprehensive care. Interprofessional collaboration has the potential to increase comprehensive patient care while also improving education and training for student clinical providers. The Intensive Comprehensive Aphasia Program (ICAP) is a growing service delivery model that infuses comprehensive care and principles of neuroplasticity, making it an ideal context for interprofessional collaboration. Aims: The purpose of this pilot project was to explore the perspectives of stroke survivors living with aphasia and interprofessional graduate student clinical providers who participated in a telehealth interprofessional psychoeducation and wellness group that was developed by healthcare providers from speech–language pathology and counseling to support aphasia recovery and living well with aphasia. Methods: A qualitative phenomenological research design was applied to explore the experiences of five stroke survivors living with aphasia, one graduate student clinical provider from speech-language pathology, and one graduate student clinical provider from counseling who participated in an Interprofessional Aphasia Community Group, that took place during the Summer 2020 University of Montana Telehealth ICAP. Content analysis procedures were applied to verbatim transcripts obtained during weekly focus groups with the stroke survivors living with aphasia and student clinical provider reflections. Results: Themes that emerged from weekly focus group transcripts suggest that stroke survivors with aphasia wanted less information during each group session, further simplification of information presented during the group sessions, and increased opportunities for discussion, communication practice, and time to connect with one another. Themes that emerged from graduate student reflections suggest that graduate student clinical providers were positively impacted by the interprofessional collaboration, improving skills, knowledge, and attitudes of their own and each other's disciplines. These themes also identified methods for improving future interprofessional collaboration in the context of an ICAP. Conclusions: This project documents what is believed to be the first telehealth delivered Interprofessional Aphasia Community Group in the context of an ICAP. Qualitative exploration of this interprofessional collaboration highlights the perspectives, voices, and experiences of stroke survivors with aphasia and graduate student clinical providers. These experiences offer insight into how collaborative care can increasingly improve participant experiences in the context of an ICAP.